Closing the loop: Towards control-aware design of adaptive real-time systems - Klaus, Tobias; Franzmann, Florian Peter; Gaukler, Maximilian; Michalka, Andreas; Ulbrich, Peter (2016 IEEE Real-Time Systems Symposium, RTSS 2016, 2016)

Data Propagation Delay Constraints in Multi-Rate Systems - Deadlines vs. Job-Level Dependencies - Klaus, Tobias; Franzmann, Florian Peter; Becker, Matthias; Ulbrich, Peter (Proceedings of the 26th International Conference on Real-Time Networks and Systems, 2018)

Design by Uncertainty: Towards the Use of Measurement Uncertainty in Real-Time Systems - Ulbrich, Peter; Franzmann, Florian Peter; Scheler, Fabian; Schröder-Preikschat, Wolfgang (Proceedings of the 7th IEEE International Symposium on Industrial Embedded Systems, 2012)
Real-time systems usually incorporate a wide variety of challenges: A control engineer, for example, aims for the highest possible control quality achievable. Here, one key element is to minimise the uncertainty of the measurements. This, to put it simple, is the noise of sensor data, which has a negative effect on control. Although measurement uncertainty is well treated in control theory, it is usually ignored in common real-time architectures where temporal properties are the prevalent criteria. Consequently, the communication between control engineers and real-time specialists is rather one way, revolving around deadlines and sampling periods. However, on closer examination, many real-time properties are derived from the measurement uncertainty aspired by the control engineer. Conversely, temporal variations, virtually inevitable in practice, can be represented as measurement uncertainty as well. Tackling the measurement uncertainty should therefore be an interdisciplinary task: The control system respects the actual run-time conditions instead of estimating them. Likewise, the real-time system considers measurement uncertainty rather than blindly sticking to deadlines. In this paper we present an uncertainty-centric approach to leverage measurement uncertainty in real-time architectures, not only at design time but also at run-time. Using measurement uncertainty as an explicit interface minimises the gap between real-time specialists and control engineers and facilitates a modular and flexible system design. Our preliminary results are promising and show the ease of use and the applicability to existing systems. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.IMMD4.design
Keywords: AORTA; ARES

From Intent to Effect: Tool-based Generation of Time-Triggered Real-Time Systems on Multi-Core Processors - Franzmann, Florian Peter; Klaus, Tobias; Ulbrich, Peter; Deinhardt, Patrick; Steffes, Benjamin; Scheler, Fabian; Schröder-Preikschat, Wolfgang (Proceedings of the 19th IEEE Symposium on Real-Time Computing (ISORC 2016), 2016)
UnivIS-Import:2016-06-01:Pub.2016.tech.IMMD.IMMD4.fromin
Keywords: RTSC; AORTA; Multi-Core; Real-Time Systems

Poster Abstract: "Closing the Loop: Towards Control-aware Design of Adaptive Real-Time Systems" - Klaus, Tobias; Franzmann, Florian Peter; Gaukler, Maximilian; Michalka, Andreas; Ulbrich, Peter (Proceedings of the 37th Real-Time Systems Symposium (RTSS '16), 2016)

React in Time: Ereignisbasierter Entwurf zeitgesteuerter verteilter Systeme - Scheler, Fabian; Klaus, Tobias; Franzmann, Florian Peter; Ulbrich, Peter; Schröder-Preikschat, Wolfgang (Betriebsysteme und Echtzeit, 2015)
UnivIS-Import:2016-06-01:Pub.2015.tech.IMMD.IMMD4.reacti

Taking Control: Modular and Adaptive Robotics Process Control Systems - Ulbrich, Peter; Franzmann, Florian Peter; Harkort, Christian; Hoffmann, Martin; Klaus, Tobias; Rebhan, Anja; Schröder-Preikschat, Wolfgang (Proceedings of the 10th IEEE International Symposium on Robotic and Sensors Environments, 2012)
Robotics systems usually comprise sophisticated sensor and actuator systems with no less complex control applications. These systems are subject to frequent modifications and extensions and have to adapt to their environment. While automation systems are tailored to particular production processes, autonomous vehicles must adaptively switch their sensors and controllers depending on environmental conditions. However, when designing and implementing the process control system, traditional control theory focuses on the control problem at hand without having this variability in mind. Thus, the resulting models and implementation artefacts are monolithic, additionally complicating the real-time system design. In this paper, we present a modularisation approach for the design of robotics process control systems, which not only aims for variability at design-time but also for adaptivity at run-time. Our approach is based on a layered control architecture, which includes an explicit interface between the two domains involved: control engineering and computer science. Our architecture provides separation of concerns in terms of independent building blocks and data flows. For example, the replacement of a sensor no longer involves the tedious modification of downstream filters and controllers. Likewise, the error-prone mapping of high-level application behaviour to the process control system can be omitted. We validated our approach by the example of an autonomous vehicle use case. Our experimental results demonstrate ease of use and the capability to maintain quality of control on par with the original monolithic design. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.IMMD4.taking
Keywords: Architecture; Software Design; Operating Systems; Robotics and Automation; Sensor Systems; Control Engineering; Measurement System Data Handling; AORTA; ARES

Usable RTOS-APIs? - Klaus, Tobias; Franzmann, Florian Peter; Engelhard, Tobias; Scheler, Fabian; Schröder-Preikschat, Wolfgang (Proceedings of the 10th Annual Workshop on Operating Systems Platforms for Embedded Real-Time Applications, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD4.usable_0
Keywords: AORTA; RTSC